(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The integration of Artificial Intelligence (AI) and language learning applications (apps) into English as a Foreign Language (EFL) classrooms has emerged as a promising avenue to enhance language acquisition. These technological tools offer a range of benefits, including personalized learning, increased accessibility, and engagement. This article explores the advantages of incorporating AI and language apps into EFL teaching, focusing on the individual learner experience, the role of gamification, and the pedagogical implications for teachers. By synthesizing current research, this article highlights how AI and language apps can complement traditional methods, provide adaptive learning pathways, and foster self-directed learning.